Integrating music and dance in education: A systematic review of emotional and social learning outcomes - Fitri, Anggia; Surya, Dhea Elvionita; Kasmahidayat, Yuliawan (Indonesian Research Journal in Education |IRJE|, 2026)
This study examines the integration of music and dance in educational contexts and their contributions to students’ emotional and social development. Using a Systematic Literature Review (SLR) guided by PRISMA procedures, 12 empirical studies published between 2015 and 2025 were analyzed from Scopus, SpringerLink, DOAJ, and Google Scholar. The findings indicate that music- and movement-based learning activities enhance emotional regulation, self-confidence, peer interaction, and classroom engagement. Group rhythmic activities promote collaboration, empathy, and social cohesion, thereby enhancing the learning environment. However, most studies focus on isolated interventions rather than systematic curricular integration. The review points out that there are structured arts-based pedagogical frameworks that align with socio-emotional learning principles and culturally responsive education, particularly in the Indonesian context. Integrating performing arts into formal education supports holistic student development and strengthens both individual competencies and collaborative learning environments.